High-energy all-fiber Er-doped femtosecond chirped-pulse amplification system seeded by nonlinear multimodal interference mode-locked fiber laser - Ahmad, Harith; Ithnahaini, M.U.M.; Samion, Muhamad Zharif; Zaini, Muhammad Khairol Annuar; Ismail, Mohammad Faizal; Bayang, Leonard; Thambiratnam, Kavintheran; Ortaç, Bülend (Academic Press Inc., 2025)
We report a high-energy femtosecond 1.5 µm all-fiber source based on chirped-pulse amplification (CPA) of soliton pulses generated by a multimodal interference. The erbium-doped mode-locked fiber seed source utilizes a nonlinear multimodal interference-based saturable absorber designed with a single-multi-single (SMS) mode fiber configuration, which can generate femtosecond soliton pulses. A commercially available ultra-high numerical aperture fiber with normal group velocity dispersion stretches the pulses up to a duration of 5.14 ps. These stretched pulses are amplified in pre- and main amplification stages to achieve watts-level average output power. Additionally, single-mode fiber (SMF) effectively compresses the pulses back down to femtosecond duration. The CPA configuration provides output power, pulse width, and repetition rate of 1.34 W, 580 fs, and 14.7 MHz, respectively, measured at a central wavelength of 1563 nm. The CPA performance yields a pulse energy of 91.2 nJ and a peak power of 157 kW. Notably, the system exhibits stable output with a minimal average output power fluctuation of 0.08 dB, indicating a stable laser performance. © 2025